Good intentions and unintended evil? Adverse effects of criminalizing clients in paid sex markets with voluntary and involuntary prostitution - Hendrik Sonnabend; Georg Stadtmann (European University Viadrina, Department of Business Administration and Economics, 2018)
Internationally, there is no consensus concerning the legal and moral judgment of prostitution. Nevertheless, there is an overwhelming agreement on the need to fight sexual slavery. We analyze how a law - introduced to punish clients of commercial sex services - affects market outcomes. More specifically, we examine how the so-called "neo-abolitionism" or "Nordic" prostitution regime impacts sexual slavery. The theoretical analysis reveals that this effect is ambiguous and crucially depends on the size of the deterrence effect and on local properties of the market demand. In addition, we highlight the conditions under which the composition of clients changes towards more risk-seeking individuals. Policy implications that arise are identified and discussed.
Keywords: K42; L51; D42; J3; 330; Prostitution; Regulation; Forced Labor; Sexual Slavery